2010
DOI: 10.1063/1.3352550
|View full text |Cite
|
Sign up to set email alerts
|

Nonequilibrium rovibrational energy distributions of hydrogen isotopologues in an expanding plasma jet

Abstract: State resolved densities of high rovibrationally excited hydrogen isotopologues H 2 , HD, and D 2 in the electronic ground state have been measured in a supersonically expanding plasma jet. The obtained state distributions differ substantially from thermal equilibrium. Moreover, the distributions are not the same for H 2 , HD, and D 2 indicating different formation and relaxation rates for each isotopologue. Mechanisms for this deviation from a Boltzmann distribution are given and compared to hydrogen reaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…From this model, the obtained rotational population distribution is very similar to the typical rotational distributions with an overpopulation of high rotational levels as observed in dissociative processes occurring in plasmas [98]. The very detailed H 2 , D 2 and HD ro-vibrational distributions measured by Gabriel et al [229] are an example of the possible influence of surface reactions in recombining plasmas.…”
Section: Surface Reactionssupporting
confidence: 76%
“…From this model, the obtained rotational population distribution is very similar to the typical rotational distributions with an overpopulation of high rotational levels as observed in dissociative processes occurring in plasmas [98]. The very detailed H 2 , D 2 and HD ro-vibrational distributions measured by Gabriel et al [229] are an example of the possible influence of surface reactions in recombining plasmas.…”
Section: Surface Reactionssupporting
confidence: 76%
“…The rotational temperature is commonly attributed to the kinetic gas temperature 56,93,94 and depends on the experimental conditions. Gabriel et al mentioned rotational temperature in the 3000-4000 K range 95 while Briefi et al indicated a two-temperature Boltzmann distribution with a low (564 K) and a high (5440 K) component 56 and Wagner et al 66 showed up lower rotational temperature, 380 K. In our reactor, in plasma-OFF condition it appears slightly above the temperature of the temperature-regulated walls of the reactor (283 K). In plasma-ON condition, it is surprisingly low even if at low pressure (8 µbar) and low electron density (∼3×10 15 m −3 ) energy transfer between electrons and neutrals through inelastic collisions is weak 96 .…”
Section: Distribution Of Energy Over Rotational and Translational Of The D2mentioning
confidence: 47%
“…Translational kinetic does also depend on the experimental condition and especially on the plasma expansion in the vacuum vessel. For example, Gabriel et al observed, in a cascaded arc 95 , kinetic energies higher than 1800 K (8 mm from the source nozzle); Wagner et al measured T trans = 300 K between 500 and 5000 W. Hence our 320 ± 20 K value, both with or without plasma, shows that the plasma expansion in our setup is low, of the same order as a thermal expansion.…”
Section: Distribution Of Energy Over Rotational and Translational Of The D2mentioning
confidence: 50%
“…Concerning the utilization of the Fulcher transition for determining the gas temperature, it is important to check which levels are described by the cold temperature and which are not. Often the first four to five rotational levels in the electronic ground state thermalize with the gas temperature (see for example [5,6,8,9,11,12]) but this strongly depends on the value of the gas temperature: When its value decreases -for example due to active cooling of the discharge vessel -the number of levels which are in thermal equilibrium with T gas also decreases due to the lower energy of the heavy particles [27,40]. As a a-priori assessment of the number of thermalized levels is hardly possible, a consideration of non-thermalized levels in the evaluation can lead to an overestimation of the gas temperature (this will be demonstrated in sections 5.1 and 5.2).…”
Section: The Fulcher-α Transition Of Molecular Hydrogenmentioning
confidence: 99%
“…In low pressure hydrogen discharges the rotational levels in the electronic ground state are known to be populated in a non-thermal way: Rotational states with low rotational quantum number follow a Boltzmann distribution according to the gas temperature of the discharge whereas those levels with high quantum number are overpopulated by several orders of magnitude (see for example [4,5,6,7,8,9] for hydrogen and [10,11,12] for deuterium). Different processes that could contribute to the overpopulation in general have been evaluated in detail in [9].…”
Section: Introductionmentioning
confidence: 99%